Sistem Informasi Pariwisata Kabupaten Kampar Berbasis Web ( Analysis) - Yasindra, Wendi; Yusnira, Yusnira; Adziral, Emon (PT Pustaka Cendekia Group, 2023)
Tourism is one of the most popular destinations for tourists today, one of the objects and tourist destinations is in Kampar Regency. Kampar Regency is very potential in the tourism sector. Both in the form of historical relics such as the Muara Takus Temple, the Koto Panjang Hydroelectric Reservoir, the Jami Mosque in Kampar District, and many other tourist objects that are quite interesting to visit. However, the problem faced is that there is still limited information to tourists about tourist objects, the current information conveyed from the website and from a blog is very limited. It is hoped that this web-based tourism information system can make it easier for the public to get information about the location of tourist objects in Kampar Regency. The programming language used is PHP Framework Laravel and MySQL as database storage media.